Pengaruh Kinerja Perusahaan Modal Ventura Dan Loan To Deposit Ratio Terhadap Pendapatan - Dwi Ermayanti Susilo; Fannia Yuke Adetiya (ARBITRASE: Journal of Economics and Accounting, 2023)
This study aims to analyze the effect of Venture Capital Company Performance (BOPO Ratio) and Loan to Deposit Ratio (LDR) on Revenue (ROA) in Companies registered with the Financial Services Authority. The research uses quantitative research methods which are carried out through data collection with secondary data, the population is the Financial Statements of Companies registered with the Financial Services Authority. The sample in this study is in the form of balance sheets and profit/loss statements of companies registered with the Financial Services Authority, data analysis using multiple linear regression statistical methods and hypothesis testing. The results show that 1) The BOPO variable affects the ROA of companies registered with the OJK in the 2019-2021 period and 2) the LDR variable affects the ROA of companies registered with the OJK in the 2019-2021 period.